Genetic diversity leads to differential inflammatory responses to cigarette smoke in mice - Md Imam Faizan; Gagandeep Kaur; Sadiya Bi Shaikh; Felix Effah; Hoshang Unwalla; Irfan Rahman (Physiological Reports)
Abstract The use of genetically diverse mouse models offers a more accurate reflection of human genetic variability, improving the translatability of findings to heterogeneous human populations. This approach is particularly valuable in understanding diverse immune responses to disease by environmental exposures. This study investigates the inflammatory responses to acute exposures to mainstream cigarette smoke (CS) and environmental tobacco smoke (ETS) in two genetically diverse mouse strains, CC002/UncJ (UNC) & Diversity Outbred (J:DO). The UM‐HET3 (HET3) mouse strain, typically used in aging intervention studies, has also been used to evaluate the translatability of this model for age‐associated pathologies. The study involves a comprehensive approach, including BALF cytokine analysis, evaluation of lung tissue architecture, assessment of macrophages and its associated proteins (MMP9 & MMP12) abundance. Several cytokines/chemokines were found to be upregulated across three strains. Notably, the UNC strain exclusively showed upregulation of TNF‐α, IL‐17A, and IL‐13, whereas the J:DO showed an upregulation in KC. The number of alveolar macrophages in the lungs of UNC mice was very low at baseline compared to other strains studied in this study, which is indicative of some inherent shift in the pulmonary immune profiles of these inbred mice. In contrast, the J:DO strain, characterized by genetic outbreeding, showed a much more robust lung macrophage response comparable to C57BL/6J. The findings provide valuable insight into how genetic diversity affects immune responses in response to acute CS/ETS exposure, with implications for understanding diverse human responses to environmental stressors in studying lung pathophysiology.